PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA MATERI PLANTAE UNTUK SISWA SMA MENGGUNAKAN ECLIPSE GALILEO - Diyan Fatmala; Upik Yelianti (BIODIK, 2016)
Abstract. This research is included for Research and Development, to produce products such as android-based learning media. The model that is used is the development of ADDIE development model. ADDIE development model has some stages which are Analysis, Design, Development, Implementation and Evaluations. Validated products by an expert team who is consisting of media experts and expert material. Subjects of tests are high school students Number 5 Jambi who are 12 students. Validation results by media experts are classified into the excellent category (83.33%) and validation results by experts are also classified into the category of material which are very good (83.33%). After doing further revisions, media is tested in small groups. Small group trial conducted high school students Number 5 Jambi who are 12 students. Based on the overall results of media analysis, media classified as excellent category (85.83%), which means a decent media is used as a medium of learning media. Learning media can be used as a learning tool that can be used independently by students. Â  Keywords: Learning Media, Android, Eclipse Galileo, Plantae.